The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1073/pnas.82.22.7590
|View full text |Cite
|
Sign up to set email alerts
|

Cap-dependent RNA splicing in a HeLa nuclear extract.

Abstract: We have studied the involvement of the 5' cap structure in the splicing of precursor mRNAs in a HeLa nuclear extract. We show that precursor mRNAs are spliced efficiently only when they possess a cap structure and that preincubation of a HeLa nuclear extract rendered the splicing reaction highly sensitive to inhibition by cap analogues. This sensitization was dependent on exogenous Mg2' but not exogenous ATP or GTP.These results demonstrate that splicing in a nuclear extract is highly dependent on the cap stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
67
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(70 citation statements)
references
References 14 publications
2
67
1
Order By: Relevance
“…The cap appears to earmark an RNA molecule for processes that are specific to Pol II transcripts. It enhances splicing, 3Ј processing, transport, and translation of mRNA (Konarska et al 1984;Edery and Sonenberg 1985;Shatkin 1985;Gilmartin et al 1988;Hamm and Mattaj 1990;Izaurralde et al 1994;Colot et al 1996;Cooke and Alwine 1996). The cap also stabilizes mRNA (Furuichi et al 1977;Green et al 1983); moreover, decapping is important for triggering degradation (Beelman and Parker 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cap appears to earmark an RNA molecule for processes that are specific to Pol II transcripts. It enhances splicing, 3Ј processing, transport, and translation of mRNA (Konarska et al 1984;Edery and Sonenberg 1985;Shatkin 1985;Gilmartin et al 1988;Hamm and Mattaj 1990;Izaurralde et al 1994;Colot et al 1996;Cooke and Alwine 1996). The cap also stabilizes mRNA (Furuichi et al 1977;Green et al 1983); moreover, decapping is important for triggering degradation (Beelman and Parker 1995).…”
mentioning
confidence: 99%
“…Previous experiments have not addressed whether capping is also integrated with transcription by a mechanism involving the CTD. Because the 5Ј cap stimulates splicing and polyadenylation (Edery and Sonenberg 1985;Izaurralde et al 1994;Cooke and Alwine 1996), it remains possible that a capping defect could contribute to reduced processing of transcripts made by Pol II with a truncated CTD. In this paper, we show that CTD truncation does, in fact, reduce mRNA capping in vivo, although this effect cannot fully account for the splicing and polyadenylation defects of transcripts made by the truncated Pol II.…”
mentioning
confidence: 99%
“…It is of particular importance in translation, at the initiation level (see references 14 and 51 for reviews). The cap also facilitates mRNA splicing (15,28) and 3' end processing (19,25) and is required for nucleocytoplasmic RNA transport (24). In addition, the cap protects mRNA against 5'-3' exonucleolytic degradation (18,21).…”
mentioning
confidence: 99%
“…Since in vitro splicing systems were developed, considerable progress has been made in understanding the mechanism of nuclear precursor mRNA (premRNA) splicing (for review, see Green 1986;Padgett et al 1986;Sharp 1987). A cap structure, m^G(5')ppp(5')N, blocking the 5' termini of many eukaryotic mRNAs has been shown to play an important role in pre-mRNA splicing (Krainer et al 1984;Konarska et al 1984;Edery and Sonenberg 1985;Ohno et al 1987). Although the requirement for the cap appears to differ slightly between whole-cell and nuclear extracts (Konarska et al 1984: Edery andSonenberg 1985), the results obtained with the in vitro splicing reaction indicate that cap recognition is an important event in the early process of the splicing reaction.…”
mentioning
confidence: 99%
“…A cap structure, m^G(5')ppp(5')N, blocking the 5' termini of many eukaryotic mRNAs has been shown to play an important role in pre-mRNA splicing (Krainer et al 1984;Konarska et al 1984;Edery and Sonenberg 1985;Ohno et al 1987). Although the requirement for the cap appears to differ slightly between whole-cell and nuclear extracts (Konarska et al 1984: Edery andSonenberg 1985), the results obtained with the in vitro splicing reaction indicate that cap recognition is an important event in the early process of the splicing reaction. By use of pre-mRNAs that contain three exons and two introns, we have shown that when a pre-mRNA is capped, the upstream intron is spliced out more efficiently than the downstream intron because of the differential effect of the cap structure on the two introns.…”
mentioning
confidence: 99%